PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (BRASSICA JUNCEA) TERHADAP PEMBERIAN BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR (POC) - Fadli, Rosnina M (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
This study aims to determine the concentration of liquid organic fertilizer (POC) is best on the growth and production of mustard. The research was conducted in the form of an experiment using a randomized block design (RAK) consisting of 4 treatments.The results showed that treatment administration concentration liquid organic fertilizer (POC) 20 ml / liter of water give the best effect against the growth parameters and production of mustard plants was observed that the average plant height of 22.74 cm, number of leaves on average 9.93 strands , the overall weight of the average weight of 80.37 grams and an average consumption of 63.62 grams.